História Viva: A Sketch-Based Interactive Storytelling System - Gheno, Felipe João; Lima, Edirlei Soares de (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2021.19631, 2021)
Storytelling is a powerful tool to convey values and enrich creativity, imagination, and critical thinking. However, digital native children are losing interest in traditional folktales as these stories now have to compete with more appealing and interactive forms of entertainment, such as videogames. New technologies allow stories to be told in different formats as digital interactions provide new experiences that can be more attractive for Generation Z children. In this context, sketch-based interaction stands out as a powerful tool to keep children interested and engaged in interactive folktales. This paper describes the design process that led to the development of a sketch-based interactive storytelling system, called História Viva, which was designed to transform traditional folktales into interactive narratives. The system explores Portuguese folktales and was designed for children within the age range of 6 to 11 years old. Preliminary results from a user study indicate that children are very receptive and entertained by the proposed interactive narrative.